Functions of code switching in youth WhatsApp chats / Nur Husna Serip Mohamad - Serip Mohamad, Nur Husna (Universiti Teknologi MARA, 2022)
This paper examines the functions of code-switching occurrences between a group of multi-ethnic youths in Malaysia. Since the population of Malaysia is ethnically and linguistically heterogeneous, code switching is a common phenomenon among these youths which has spread into the online mode of communication. WhatsApp chats from a total of 24 respondents was collected from participants of various background, mainly Malay, Chinese and Indian ethnic groups. A qualitative methodology was employed wherein an online interview was conducted to analyse their motives underlying the code-switching phenomenon. The functions of code- switching were further analysed using a conceptual framework developed by the researcher that was adapted from Appel and Muysken (2005) and Hoffman's (1991) functional model of code-switching. The yielded findings postulate that the participants in this study code-switched in the WhatsApp Messenger mostly for emphatic function and interjections. However, the paper propose that habitual code switching might encourage the code-switching phenomenon, since both English and Bahasa Malaysia play a huge role in their daily communication. Code switching behaviour also indicates their bi-multilingual identity as Malaysians.